2019
DOI: 10.3390/biom9100613
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Sclerotinia sclerotiorum by the Induction of Systemic Resistance and Regulation of Antioxidant Pathways in Tomato Using Fengycin Produced by Bacillus amyloliquefaciens FZB42

Abstract: Lipopeptides from Bacillus species exhibit promising biological control activity against plant pathogens. This study aimed to explore the potential of purified fengycin to induce systemic resistance in tomato against Sclerotinia sclerotiorum. Bacillus amyloliquefaciens FZB42, its mutant AK1S, and their corresponding metabolites showed in vitro inhibition of S. sclerotiorum mycelium. Fengycin derived from an AK1S mutant was purified and identified through HPLC and MALDI-TOF-MS, respectively. Scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 81 publications
4
72
0
Order By: Relevance
“…Exposure to toxic compounds that elicit ROS production resulted in abnormal cell homeostasis and finally death [ 36 , 37 ]. The current results show that MIV, 2-undecanone (2-UD) and dimethyl disulfide (DMDS) with strong nematicidal activity-induced ROS in nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to toxic compounds that elicit ROS production resulted in abnormal cell homeostasis and finally death [ 36 , 37 ]. The current results show that MIV, 2-undecanone (2-UD) and dimethyl disulfide (DMDS) with strong nematicidal activity-induced ROS in nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…Induction of systemic resistance and/or plant defenses by other CLPs produced by biocontrol bacilli has also been occasionally reported. In tomato and grapevine, fengycin triggered ISR against B. cinerea and Plasmopara viticola ( Farzand et al, 2019 ; Li et al, 2019 ), while CLPs from the iturin group ( Figure 1-3 ) were shown to have a similar role in strawberry ( Yamamoto et al, 2015 ), cotton ( Han et al, 2015 ), grapevine ( Farace et al, 2015 ) and Arabidopsis ( Wu et al, 2018 ). Additionally illustrating the dependence of CLP-mediated ISR on the plant organ, iturin showed bioactivity on roots at concentration of 50 μM, whereas it was active already at 1–10 μM when applied on leaves ( Han et al, 2015 ; Kawagoe et al, 2015 ; Yamamoto et al, 2015 ; Park et al, 2016 ).…”
Section: Pgpr Metabolites Identified As Elicitors Of Plant Systemic Rmentioning
confidence: 99%
“…To date, the active mechanism of fengycins is less well known compared with iturins and surfactins. The possible mechanism for the antifungal activity of fengycins is that they interact with sterol and phospholipid molecules in membranes and thus alter the structure and permeability of the fungal cell membrane (Farzand et al, 2019;Hanif et al, 2019). However, the mechanism of interaction may vary and depend on the structural features of fengycins and pathogen species (Kaur et al, 2017;Sarwar et al, 2018).…”
Section: Possible Assignment Bmentioning
confidence: 99%